Hypothermia and normothermia effects on mortality rate of cardiopulmonary bypass - Ali Rahdari; Reza Jalaeian Taghaddomi; Alireza Sabzevari; Shabnam Imannezhad; Mohsen Akhondi (Reviews in Clinical Medicine, 2016)
Introduction: Cardiopulmonary bypass is associated with higher risk of mortality and morbidity, thus it should be investigated regarding the major risk factors. Temperature management have a significant role in postoperative cerebral and neurological complications; however the optimum temperature during cardiopulmonary surgery is not certainly detected. This systematic review has investigated the differences between hypothermia and normothermia regarding postoperative mortality. Method: PubMed was searched for the relevant articles. Only English language articles were included with no time limitation. Data regarding in-hospital patient deaths provided in each article mostly within 30 days after the surgery, were extracted and compared based on relative risk reduction (RRR), absolute risk reduction (ARR), and number needed to treat (NNT).Result: Totally, 28 articles were retrieved and extracted. The mortality rate was zero in hypothermic and normotehrmic groups of 8/28 included studies, thus the RRR, ARR, and NNT could not be calculated. There were no significant differences between investigated groups of each included studies regarding the patients’ age, gender, and preoperative conditions.Conclusions: No significant difference was obtained between two studied groups. Similar prevalence of death observed between hypothermic and normothermic groups might be due to the sample size of studies, or the subsequent cares performed in intensive care units that assist to reduce the postoperative mortality rate. According to the obtained results, both of these procedures might be similarly safe regarding mortality rate.